Assessment of the Green Hydrogen Value Chain in Cases of the Local Industry in Chile Applying an Optimization Model - Serafini, D; Garrido-Lazo, R; Rodriguez-Machuca, P (Elsevier Ltd, 2024)
This study assessed the feasibility of integrating a green hydrogen value chain into the local industry, examining two case studies by comparing four scenarios. The optimization focused on generating electricity from stationary renewable sources, such as solar or through Power Purchase Agreements, to produce sufficient hydrogen in electrolyzers. Current demand profiles, renewable participation targets, electricity supply sources, levelized costs of energy and hydrogen, and technology options were considered. The most cost-effective scenario showed a levelized cost of energy of 0.032 and 0.05 US$/kWh and a hydrogen cost below 1.0 US$/kgH2 for cases 1 and 2, respectively. A sensitivity analysis highlighted the critical influence of fuel cell technology on cost modification, underscoring the importance of focusing cost reduction strategies on these technologies to enhance the economic viability of the green hydrogen value chain. Specifically, a high sensitivity towards reducing the levelized costs of energy and hydrogen in the port sector with adjustments in fuel cell technology costs was identified, indicating the need for specific policies and supports to facilitate their adoption. © 2024 The Authors